Exact integration for stress evaluation in the boundary element analysis of two-dimensional elastostatics - Zhang, X.; Zhang, X.
This paper presents an exact integration to evaluate the stress in the boundary element analysis of two-dimensional elastostatics. The boundary is discretized by straight segment and the exact integration is derived for those that the physical variables on the boundary are approximated by constant, discontinuous linear and discontinuous quadratic elements, respectively. The accuracy of the exact integration is verified against two examples and the results show that the exact integration can accurately calculate the stress on the boundary by simply treating boundary points as special interior points.
Keywords: EXACT INTEGRATION; STRESS EVALUATION; NEARLY-SINGULAR INTEGRAL; DISCONTINUOUS BOUNDARY ELEMENTS